Síndrome de Burnout em atletas infanto juvenis - Santos, Ana Clecia Alves dos (2015)
The Burnout syndrome is a topic that is currently presented as a major problem that affects the labor activity in several areas, including athletes. Known as syndrome of physical and psycho-social breakdown has become the object of study Psychology. However, in Sport Psychology is little explored, and there is little literature on the subject, which makes the knowledge and understanding of the syndrome. This research it is a descriptive study of transversal and quantitative approach, which was attended by 194 athletes from different states, of both sexes, with an age range of 14 to 17 years, swimmers and volleyball. To collect data we used two instruments: one demographic data questionnaire and the Burnout Questionnaire for Athletes - BQA. Data analysis consisted of descriptive analysis and comparison of variables, sex, sport, education, sports injury, age and time as a federated athlete, using the nonparametric Kruskal-Wallis and Mann Whitney. The results showed that in general, the athletes present in the study were not in a risk state for Burnout, with an overall average of 2.09 points corresponding to a feeling frequency between Seldom and Sometimes. Concerning the size Physical and Emotional Exhaustion in variable sport, there were differences between them, which showed statistically significant (p = ˂0,001), even with averages of 1.88 (swimming) and 1.58 (volleyball), respectively related to a frequency between Hardly Ever and Rarely. The size Reduced Sense of Accomplishment showed higher rates in all variables, with a frequency of feelings related to Rarely to Sometimes average ranging from 2.50 to 2.59. We conclude that the juvenile athletes swimming and volleyball did not show a frequency of high feelings, referring to Burnout.